2012
DOI: 10.1002/app.38010
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationship for dihydromyricetin as a new natural antioxidant in polymer

Abstract: Dihydromyricetin (DMY), a natural product, was used as antioxidant in ethylene vinyl acetate copolymer (EVA) in our laboratory. Oxidation induction temperature (OIT) of EVA with the antioxidant of DMY and effect of pH on OIT was measured by means of differential scanning calorimeter (DSC). The mechanism on that antioxidation of DMY in EVA is produced on basis of determination of UV-Vis absorption, nuclear magnetic resonance (NMR) and the experiment of reacting the pyrogallic (PA) and DMY, respectively, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The chemical nature of these compounds depends on their structural class, degree of hydroxylation, other substitutions and conjugations, and degree of polymerization (Kumar and Pandey, ). It has been reported that the ortho‐trihydroxyl group in DMY has anti‐oxidative activity; while the hydroxyl group of DMY not only displays reversibility in acidic or alkaline medium but also affects the anti‐oxidative ability (Xin et al ., ). Previous studies showed that DMY has a variety of pharmacological activities, such as anti‐cancer, anti‐inflammation, and so on.…”
Section: Discussionmentioning
confidence: 97%
“…The chemical nature of these compounds depends on their structural class, degree of hydroxylation, other substitutions and conjugations, and degree of polymerization (Kumar and Pandey, ). It has been reported that the ortho‐trihydroxyl group in DMY has anti‐oxidative activity; while the hydroxyl group of DMY not only displays reversibility in acidic or alkaline medium but also affects the anti‐oxidative ability (Xin et al ., ). Previous studies showed that DMY has a variety of pharmacological activities, such as anti‐cancer, anti‐inflammation, and so on.…”
Section: Discussionmentioning
confidence: 97%
“…And recent studies have demonstrated its pharmacological effects such as antioxidative, anti-inflammatory, antihypertensive, antiviral and hepatoprotective activities [2]. Dihydromyricetin (DMY), a dihydro flavonol compound found as the most abundant (approximately 30%) and bioactive constituent in vine tea, has been demonstrated to posses numerous pharmacological activities including anti-oxidant [3][4][5], anti-cancer [6][7][8], anti-inflammation [9], anti-hypertension [10], anti-fatigue [11], anti-alcoholic intoxication [12] and hepatoprotective effects [13].…”
Section: Introductionmentioning
confidence: 99%
“…22 The ortho-trihydroxyl group (hydroxyl in the C-3’, 4’, and 5’ position) in B-ring of DHM has been demonstrated to have strong effect against free radicals and provide an antioxidant defense. 23, 24…”
Section: Discussionmentioning
confidence: 99%